Export boom and economic performance: Bolivia 2004-2015 - Melissa Liza; Juan Antonio Morales Anaya (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2018)
The supercycle of high commodity prices has had profound impacts on the Bolivian economy. We have investigated the relations of commodity prices with the main indicators of macroeconomic performance. We have found significant ties in our statistical analysis. An important question that we address concerns the consequences of the transitory export boom on the long term rate of growth of the economy. Also, given the importance of fiscal linkages with windfall income, we examined the procyclality of public expenditures based on an analysis of correlations of the cyclical components. We find positive but weak correlations. With export booms, consumption increases but also saving rates. Savings have been invested in foreign assets and, to a large extent, in construction. We find that commodity prices and per capita value added in the construction sector are co-integrated, suggesting a long term relationship. Also we looked into the real linkages of the hydrocarbons sector with other sectors of the economy through an Input-Output analysis. Finally, we have conducted a set of simulations, with a small Computable General Equilibrium Model adapted to the Bolivian conditions, to trace the domestic price and quantity effects of the commodity price increases.
Keywords: C32; C67; C68; E60; E62; F63; 330; price supercycle; transitory trade shocks; fiscal effects; procyclality; Bolivian economy